2002
DOI: 10.1128/jvi.76.5.2113-2122.2002
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Translation Initiation Factor eIF4B with the Poliovirus Internal Ribosome Entry Site

Abstract: Poliovirus translation is initiated at the internal ribosome entry site (IRES). Most likely involving the action of standard initiation factors, this highly structured cis element in the 5 noncoding region of the viral RNA guides the ribosome to an internal silent AUG. The actual start codon for viral protein synthesis further downstream is then reached by ribosomal scanning. In this study we show that two of the secondary structure elements of the poliovirus IRES, domain V and, to a minor extent, domain VI, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 48 publications
(50 reference statements)
1
47
1
Order By: Relevance
“…Some herpesviral genes are encoded on polycistronic mRNA whose translation relies on the IRES. eIF4B is known to interact with the IRESs of several RNA viruses (71)(72)(73)(74)(75) and the virion host shutoff protein of herpesvirus simplex 1 (76). How eIF4B is involved in the translation regulation of herpesviral mRNAs remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Some herpesviral genes are encoded on polycistronic mRNA whose translation relies on the IRES. eIF4B is known to interact with the IRESs of several RNA viruses (71)(72)(73)(74)(75) and the virion host shutoff protein of herpesvirus simplex 1 (76). How eIF4B is involved in the translation regulation of herpesviral mRNAs remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…pFM is renamed from pM12 (13) for clarity; it contains the FMDV IRES and the firefly luciferase gene. pMPolio (17) contains downstream of an SP6 polymerase promoter the complete poliovirus type 1 (Mahoney) 5Ј-UTR sequence with the authentic initiator AUG fused to the Fluc coding sequence. For construction of pRL-FM-wt, pRL-FM-up-CG, and pRL-FM-up-4, the CAT reporter gene was removed from the respective pCAT-FM-plasmid, and the T7 polymerase promoter sequence together with the Renilla luciferase (Rluc) gene from phRL-null (Promega) were inserted.…”
Section: Methodsmentioning
confidence: 99%
“…6A). In contrast to the picornavirus IRES elements, the HCV IRES can bind to the small ribosomal subunit in the absence of virtually any translation initiation factors (19,20), whereas binding of ribosomes to picornavirus IRES elements requires initiation factors (9,10,13,17,18). The results of translation at different K ϩ concentrations (Fig.…”
Section: A Picornavirus Ires Can Enhance Translation Of An Upstream Rmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, poliovirus infection of permissive cells results in the cleavage of eIF4G by viral 2A proteinase that removes the eIF4E-binding domain and abrogates cap-dependent translation. Yet, IRES-mediated translation of picornavirus mRNA still occurs through the binding of truncated eIF4G, eIF4B, and the recruitment of 40S ribosomal subunits (Hambidge and Sarnow 1992;Ochs et al 2002). Also, it has been demonstrated that activation of both Apaf-1 and DAP5 IRES elements during apoptosis is caspase-3 dependent and mediated by the proteolytically cleaved forms of eIF4G and DAP5 (i.e., eIF4G(p76) and DAP5(p86), respectively; Henis- Korenblit et al 2002).…”
Section: Ires-mediated Translation Of C-iap1 Mrnamentioning
confidence: 99%